Applying The Extension Of Technology Acceptance Model (E-TAM) in analysing the customer's intention in using online islamic banking services in Malaysia / Nora Fadilah Ismail - Ismail, Nora Fadilah (2019)
Customer's intention in using online Islamic banking services has been one of the crucial concerns for each and every institution either by banking institutions or e-commerce companies that are rapidly developing nowadays. Therefore, analysing the customer's intention in using online Islamic banking services assists these institutions in finding alternatives for the purpos of attracting new customers either directly or indirectly. This study attempts to investigate the determinants that affect the customer's intention in using online Islamic banking services. This study was carried out by conducting a survey through questionnaire distribution to 149 of respondents. The factors that were investigated in this study are perceived usefulness, perceived ease of use, perceived enjoyment, perceived credibility and social norms. The relevant variables were adopted by this study as they were frequently used in previous studies. The study has identified that the customers' level of intention is high at the level of 4.8322 based on the four likert scale. This study also showed that the perceived credibility is the most significant determinants that influences customers' intention in using online Islamic banking services.